Addition of Mackerel Fish Bone Meal as a Source of Calcium on the Quality of Mackerel Biscuits - Solissa, Hermelina; Risakotta, Tesalonika K. (Fakultas Pertanian, Universitas Muhammadiyah Maluku Utara, 2024)
Calcium is a mineral that is really needed by the human body, especially for growth. Utilizing fish bone waste as a source of calcium is an alternative in order to provide a nutrient-rich food source while reducing the negative impact of environmental pollution resulting from the disposal of waste from the fish processing industry. Fish bone waste has the potential to be used as a source of calcium in the human body and can be used in processing food products that are easily accepted by the general public. The resulting biscuits were then tested for calcium content, proximate content (moisture, ash, fat, protein and carbohydrate content) and a liking level test (organoleptic including color, taste, smell and texture). The best treatment is seen based on the highest calcium level value. The results showed that the addition of fish bone meal to biscuits resulted in a water content in the P4 treatment of 5.12%, a protein content of 12.5%, a fat content of 22.5% and a carbohydrate content of 50.8%. The sample formulation was obtained based on organoleptic acceptance tests in making biscuits that were fortified with mackerel fish bone flour, namely in treatment P0 with a formulation of 5 grams of mackerel bone flour, while for texture it was P4 with a formulation of 20 grams of mackerel bone flour.